ТАЪЛИМ-ТАРБИЯ ЖАРАЁНИДА ЎСМИРЛАР ХУЛҚ-АТВОРИНИ НАМОЁН БЎЛИШИНИНГ ИЖТИМОИЙ ‒ ПСИХОЛОГИК АСПЕКТЛАРИ (Scientific journal of the Fergana State University, 2023)
This article is devoted to learn teenagers’ behavior as social-psychological phenomena. Also influence this phenomena to education process.